Digital Literacy toward Historical Knowledge: Implementation of the Bukittinggi City History Website as an Educational Technology - Fatimah, Siti; Hidayat, Hendra; Sulistiyono, Singgih Tri; Alhadi, Zikri; Firza, Firza (JOIV : International Journal on Informatics Visualization, 2023)
This research aims to identify the challenges and opportunities in integrating digital literacy skills into history education. This research focuses on understanding educators' difficulties in integrating digital technologies into the traditional history curriculum. Educational technology as a means and facility to support education and learning is no exception for historical knowledge through access to historical websites. This study analyses digital literacy toward historical knowledge using the Bukittinggi City history website. This research is quantitative research with a survey approach with closed-ended questions. The research population is the millennial generation in Indonesia. Samples were taken with a non-probability sampling approach with purposive sampling. This study involved 831 respondents spread throughout Indonesia. The data analysis technique is partial Least Square Structural Equation Modelling (PLS-SEM). The results showed no difference in historical knowledge scores between males and girls. With a value of 0.697 and a 69.7% variance, the coefficient of determination (R2) result demonstrates significant volatility in historical knowledge. Additionally, Q2's value serves as a gauge for the model's predictive usefulness. The predictive relevance of the model's independent variables was assessed using the predictive relevance test (Q2). Men might be more adept at using online resources to broaden their knowledge of the city's past. Understanding the disparities in digital literacy between men and women will significantly impact the design of educational and literacy programs in Bukittinggi. Enhancing digital literacy can promote access to and understanding of the city's history, especially among women